DETERMINANTS OF VEGETABLE FARMER’S INCOME IN NGABAB VILLAGE, PUJON SUBDISTRICT THE REGENCY OF MALANG - Mardika Belapati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
Nowadays, the development of agriculture is still considered as the most important thing from all of economic developments in developing countries such as Indonesia, because it has abundant of natural resources and big potential of contribution to the national income. However, the fact until recently a majority of farmers in Indonesia are categorized as poor people. Unfortunately, that the agriculture sector even has big contributions of labor absorsion but the prosperity of farmers is still relatively low. The purpose of this research is to do an analysis of variables which effect on vegetable farmer’s income in Ngabab village. Those variables X1= Education Level, X2=Land Capacious, X3=Capital, X4=Labor. The research method which used is quantitative descriptive with random sampling technique (simple). Analysis method which used is multiple regression analysis. The result of the analysis shows that vegetable farmer’s income in Ngabab village can be explained as well by variable education level, land capacious, capital and labor. Through data analysis and statistic test, these show that from those four independent variables, apparently only three variables of which have significant effect on vegetable farmer’s income. Those are land capacious (X2), capital (X3) and labor (X4). Meanwhile variable education level has no significant effect on vegetable farmer’s income. Keywords : Farmer’s income, Education Level, Land Capacious, Capital, Labor